BANDUNG'S OFFICE OF INDUSTRY AND TRADE COOPERATIVES' STRATEGY FOR INCREASING THE COMPETITIVENESS OF FOOD MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) - Sutrisno Sutrisno (Jurnal Ekonomi, 2022)
This study aims to describe the strategies implemented by the Koperindag Service in increasing the competitiveness of MSME Food in the City of Bandung, as well as the obstacles encountered by the Koperindag Office in increasing the competitiveness of MSME Food in the City of Bandung. When conducting a study, the descriptive qualitative research method is used in the form of a detailed description of the location, situation, event, or what is observed. Data collection methods include interviews, on-site observation, and documentation. According to the findings of this study, the Koperindag Service employs three types of strategies in increasing the competitiveness of MSME Food in the City of Bandung. The first step is to strengthen the strategy by organizing product promotion activities. Second, an empowerment strategy that includes entrepreneurship training, outreach, and packaging advice. Third, by facilitating increased competitiveness of Food SMEs, programs to foster a favorable business climate will be strengthened. The lack of resources is a challenge for the Koperindag Service in